2012
DOI: 10.2119/molmed.2011.00458
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-Ribose) Transferase/Polymerase-1-Deficient Mice Resistant to Age-Dependent Decrease in β-Cell Proliferation

Abstract: Basal and adaptive β-cell regeneration capacity declines with old age, but the underlying molecular mechanisms remain incompletely understood. Poly (adenosine diphosphate [ADP]-ribose) polymerase 1 (PARP-1) is considered a multifunctional enzyme and transcription factor that regulates pancreatic β-cell death, regeneration and insulin secretion. We analyzed the capacity of β-cell regeneration in 2-month-old (young) and 12-month-old (old) wild-type (WT) and PARP-1 -/-mice before and after low-dose streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Several recent studies have reported that PARP-1 could negatively regulate bone resorption and that PARP inhibition could suppress the osteogenic differentiation of osteosarcoma cells and mouse mesenchymal stem cells 18,19 . We have shown that PARP-1 functions as a crucial modulator of NF-kB activity and that PARP-1 inhibition attenuates inflammatory responses during atherogenesis 20,21 and diabetic complications 22 . However, the potential link between PARP-1 regulation and diabetes-induced atherosclerotic calcification has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported that PARP-1 could negatively regulate bone resorption and that PARP inhibition could suppress the osteogenic differentiation of osteosarcoma cells and mouse mesenchymal stem cells 18,19 . We have shown that PARP-1 functions as a crucial modulator of NF-kB activity and that PARP-1 inhibition attenuates inflammatory responses during atherogenesis 20,21 and diabetic complications 22 . However, the potential link between PARP-1 regulation and diabetes-induced atherosclerotic calcification has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian PARP-1 is a 116-kDa protein that catalyzes the covalent attachment of poly(ADP-ribose) polymers on itself and on other acceptor proteins (16). PARP-1 contains three major functional units, including the DNA-binding domain comprised of two zinc finger motifs, the automodification domain that functions as the target of covalent automodification, and the catalytic domain (17).…”
Section: Biochemical Identification Of the Allele-binding Nuclear Actmentioning
confidence: 99%
“…To assess and distinguish between the roles of PARP1 protein and its activity in the stem cell-mediated islet regeneration potential, we first compared pancreatic histology for islet development in PARP1 knockout and wild-type mice produced in the 129SV-B6 strain background. An age-dependent study from Zhang et al 22 has reported no effect of PARP-1 deletion on glucose homeostasis and functional regulation of β cells in young and old KO mice despite the whole body PARP1 knockout. Considering non-affected glucose metabolism, we expanded our investigation to delineate the developmental aspects of islet formation and pancreas architecture in PARP1 wild-type and KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…The role of PARPs in diabetes has been explored for the last thirty years, with early studies employing PARP-inhibitors in isolated β cell function 15 , 34 , while later reports investigated the action using PARP1 −/− mice or derived cells 17 20 . The prime emphasis was, however, overlaid on PARP1 for exploring the role in DNA repair during β cell death, survival, physiology, and insulin secretion 6 , 22 , 29 . Moreover, most minor attempts were made to understand the possible mode of action of PARP1 in β cell regeneration or stem cell-derived differentiation.…”
Section: Discussionmentioning
confidence: 99%